Growth, survival and intactness of green mud crab (Scylla Paramamosain) broodstock under different captive grow out protocols (SAARC Journal of Agriculture, 2018)
Development of broodstock of the green mud crab (Scylla paramamosain) was assessed under three different captive growout protocols viz. in the open fibre glass tanks (T1), in plastic boxes (T2) floating on fibre glass tanks and in plastic drawer/compartment (T3) for a period of 5 months under the Centre for Marine and Coastal Studies (CEMACS), Universitiy Sains Malaysia (USM). The male (M) and female (F) mud crab were cultured separately to maintain virginity. Suitability of both the sexes were evaluated considering the weight gain (size), survival and intactness of limbs during harvesting. Result of the present study revealed that, irrespectives of growout protocols, growth of mud crab happened following the sigmoid pattern. A noticeable intersexual weight attainment was observed with significantlyhigher (p